Franz Liszt: Brieven van een reiziger - Liszt, Franz 1811-1886; Ophof, Tineke; Onderdenwijngaard, Toos (Amsterdam Antwerpen Atlas, 1994)
Originally published in magazines from 1837 to 1841, Lettres d'un bachelier ès musique is one of the few texts Liszt wrote and published directly in French. An exceptional document on the musical and artistic life of the mid-nineteenth century, these fourteen “travelogues” are addressed from Paris, Geneva and Milan to George Sand, Henri Heine and Hector Berlioz. They are among the great, little-known pages of French Romantic literature.
Keywords: 19th Century (1801-1900); Correspondence; Composer; Travel